Análisis productivo y económico del cultivo de cacao theobroma cacao l. en la asociación de productores de la parroquia “San Carlos” Cantón, Joya De Los Sachas, provincia de Orellana. - Torres Velasquez, Ana Veronica (2016)
This research called Productive and Economic Analysis of cocoa Theobroma cacao L. In the Association of Producers of the parish "San Carlos" Canton, Joya de los Sachas province of Orellana. He had as objectives. A diagnosis of the cultivation of cocoa production system, determine the profitability of cocoa production per hectare. And dissemination of research results to the community involved. Regardless of varieties cocoa production is necessary to improve the quality as it is considered one of the highest revenue for production. The profitability of cocoa offers the producer in the early years combined with the planting of fruit and timber thus giving added value. The results benefit farmers association with favorable interests. For the development of the methodology, study methods used; analytical, exploratory, descriptive, explanatory, and direct observation techniques, survey, document review, field. The results for productive analysis in relation to plants per hectare are 625 planted at 4 x4 giving a raw material production 25 scrape out and 40 pounds per plant per year since the varieties that exists in this area is the super tree mostly be a quality product it is containing aroma and is sold at a price of $ 105 per quintal. For productive analysis, crop management cocoa by farmers 46% have 1 to 2 hectares of cultivation, this means that are small and medium producers who handle areas that do not supply the demand needed by the domestic market and require more resources to invest in their land. In relation to the management of cocoa varieties has increased production cocoa graft national super tree variety with 58%, this variety that is resistant to pests and diseases and increased production yield compared to other varieties. As regards the result of pruning cocoa farming shows that 44% have no knowledge in handling prunings. This means that farmers must be trained to perform the pruning, since this activity is very important that the plant uses the nutrient that provides the soil and produce as much cob. The results of the investment yield on cost of production of cocoa per hectare production cost per quintal of cacao, production costs per craft dough cocoa producers association San Carlos show us that owns 11.72% return. Which means it is estimated that a small business that gets good profits. Harvest and post-harvest cocoa survey of farmers 51% say they have little knowledge on the topic, crop post-the same as agreed that handle different methods of drying of cocoa and only through centralization of processing may ensure uniformity in the product quality. Because often this work is done in small quantities according to their need for liquidity, which prevents achieving optimal quality standards. It is recommended MAGAP managed through the implementation and improvement of productive agricultural activities on the cocoa crop management to small and medium farmers for better economic gains. It is recommended to manage the Association technical advice to stimulate, promote local development on the profitability of national plant variety super tree grafting of cocoa.